An In-Vitro Comparative Study To Investigate The Different Bonding Strengths Of Resin Modified Glass Ionomer Cement Using Different Conditioning Materials (Journal of Hama University, 2021)
Determining the best way to prepare human dentin (which achieves the greatest bond strength) before applying the resin-modified glass ionomer cement as a reparative material, as this contributes to the clinical success of the resin-modified glass ionomer cement. The research sample consisted of 100 human premolars, which were extracted for orthodontics reasons ( intact crowns )It was divided evenly randomly into two subsamples, then each subsample was divided ,according to the method of preparing the followed dentin surface for five equal groups containing only 10 premolars (conditioning the surface of dentin with phosphorus acid 37% then applying cement without a bond system, conditioning the surface of dentin with phosphorus acid 37% and then applying a bond system, then applying the cement, applying the cement directly without contouring, no scratching, no applying of the bond system.A horizontal cut was performed for the crowns of the teeth of the sample to detect the dentin, and then casting them into acrylic molds which is suitable for the measurements of the stabilization cell of mechanical testing devices, then lathing a special cylindrical mold to apply the cement samples, and the tensile and shear tests were carried out on these samples.The study found that the value of the bond strength (in megapixel ) in the group of conditioning of the surface of dentin with phosphorus acid 37% and then applying of the bond system was greater compared to the remaining four groups. Accordingly, we advise older practitioners to use this method of preparation of the dentin surface during applying of resin-modified glass ionomer cement